The effect of international energy prices on energy production in Sichuan, China. (November 2020) - Zou, Gaolu; Chau, Kwong Wing
Abstract: Sichuan Province is China's leading natural gas and hydropower producer. This article tests for the effects of international energy (nominal) prices on natural gas and hydropower production in Sichuan. Monthly data cover the period from April 2002 to June 2019. This study conducts unit root tests using the standard augmented Dickey–Fuller (ADF) test, the Phillips–Perron (PP) test, and the Dickey–Fuller generalized least squared (GLS) test suggested by Elliott, Rothenberg and Stock (ERS), and the Perron break date innovational outlier (IO) Model C. It tests for long-run equilibrium using the Johansen multivariate method and Phillips–Ouliaris technique. It tests for weak exogeneity and estimates error-correction models (ECMs) and vector-autoregressive models (VARs). Overall, in the long run, both international spot and futures gas prices slightly and positively impacted the production of gas and hydropower. Differences between the spot and futures gas price effects were minor. International crude oil prices had insignificant effects on energy production. Energy production was gas price-inelastic. Long-run spot and futures gas price elasticities of gas output were 0.192 and 0.186, respectively. Given the strong governmental support for energy prices, Sichuan's gas market has partially integrated into the global gas market. We suggest that, in the long run, both international futures and spot gas prices can be considered as an exogenous variable predicting changes in gas production. International futures gas prices can be a short-run factor predicting gas production. Gas production appears to serve as a long-run substitute for hydropower production; accordingly, with the growing gas supply, hydropower oversupply in Sichuan may become increasingly severe in the long run.